A Multi-Functional Electrolyte for Lithium-Ion Batteries: II. Boiling Electrochemical Performance. Issue 9 (9th July 2016) - Westhoff, Kevin; Bandhauer, Todd
Abstract : The high thermal conduction resistances of lithium-ion batteries (LIBs) severely limit the effectiveness of conventional external thermal management systems (TMSs). One potential solution is to remove heat locally inside the cell by evaporating a volatile component of a multi-functional electrolyte (MFE). Low boiling point hydrofluoroethers (HFE) were first used by Arai to increase LIB electrolyte flash points, and have been proven to be compatible with LIB chemistry. HFE-7000 and ethyl methyl carbonate (EMC) 1:1 by volume are used to solvate 1.0 M LiTFSI to produce a MFE for the proposed cooling system. In part I, the non-boiling electrochemical performance of the MFE was compared to a carbonate-only electrolyte. The results showed that despite its high volatility, HFE-7000 is a feasible co-solvent for LIBs. In the present study, copper antimonide (Cu2 Sb) and lithium iron phosphate (LiFePO4 ) are used in a full cell architecture with the MFE in a custom electrolyte boiling facility. The facility enables direct viewing of the vapor generation within the full cell and characterizes the galvanostatic electrochemical performance. Test results show that the LFP/Cu2 Sb cell is capable of operation even when a portion of the more volatile HFE-7000 is continuously evaporated under an extreme heat flux.